The Reality Of Training Courses In The Curriculum Developed For Teacher Tutor In Lattakia Governorate - مسلم سناء جبرائيل (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to identify the reality of the training courses in the curricula developed for the proxy teachers in Lattakia governorate, and the effect of the variables (gender, following previous training courses, and the number of years of previous experience) on that, and in order to achieve the research objectives, the descriptive and analytical approach was used, by designing a questionnaire that was formed Of (55) phrases distributed into (7) dimensions, they were applied to (241) male and female teachers, and among the most prominent results of the research were: The degree of approval of the trainees’ research sample regarding the course objectives was high. - The degree of approval of the trainees’ members of the research sample on the axes (course content, trainers and training methods, benefit from training topics, course timing and duration) was moderate The degree of approval of the trainees’ research sample on the axis (course center) was low. - The absence of statistically significant differences in the reality of the training courses in the curricula developed for teachers’ Tutor in Lattakia governorate according to the two variables (gender, number of years of previous experience). - There are no statistically significant differences in the reality of training courses in the curricula developed for teachers tutor in the governorate of Lattakia according to the variable (following previous training courses), with the exception of the dimension (benefiting from training topics), where differences were found in favor of teachers who followed one or more courses.